PERANCANGAN KOMIK SEJARAH PERANG PADRI DI SUMATERA BARAT ” THE HEROES OF PADRI” - PUJIAMA YUDHA, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Padri War comic tells the story of a war between brothers (Padri War). This story happened in West Sumatra in 1803-1838. This historical event made in comic form, aims toincrease interest in reading the youth to learn history through the medium of interest.Based on the problems, they invented the design of comics history